Playing with bonbon fire : a Southern chocolate shop mystery - St. James, Dorothy (St. James, Dorothy. Southern chocolate shop mystery., 2018)
Chocoholic Charity Penn must smoke out the killer to stop her newly inherited beachside chocolate shop from going up in flames.